10 Years of Adult Learning: Content Analysis of an Academic Journal. (February 2017) - Cherrstrom, Catherine A.; Robbins, Stacey E.; Bixby, John
Academic publications provide insights into a discipline's history, knowledge base, and research norms, and thus analyzing publication activity provides learning about the field of study. To learn more about the field of adult and continuing education, this study used content analysis to examine 10 years of Adult Learning from 2006 through 2015, providing insights into the field, major findings related to journal issues; article authorship, keywords, purpose, frameworks, and research design; and five prevalent themes and trends.